Pengaruh Pengetahuan Produk dan Citra Merek Terhadap Keputusan Pembelian Skincare - Mahendra, Aditya Rifqi; Sriminarti, Nurul (Journal of Business and Economics Research (JBE), 2025)
This study aims to determine how the influence of product knowledge and brand image on purchasing decisions for skincare Skintific. This research is included in the type of quantitative research. The method used in collecting data in this study was carried out by distributing questionnaires to 100 skincare Skintific customer respondents. The research data analysis method used is multiple linear regression analysis method. The results of this study state that the product knowledge variable has a tcount value of 2.156. So that the results obtained tcount> ttable where 2.156> 0.201 besides that the significant value is 0.023 Value 0.023 <0.05. Then the hypothesis is accepted. This shows that product knowledge has a positive effect on purchasing decisions. The results showed that the better the product knowledge, the more purchasing decisions will increase. The results of this study state that the brand image variable has a tcount value of 7.208. So that the results obtained tcount> ttable where 7.208> 0.201 besides that it is significant at 0.000 Value 0.000 <0.05. Then the hypothesis is accepted. This shows that brand image has a positive effect on purchasing decisions. The better the brand image, the more purchasing decisions will increase.